STUDI EKSPERIMEN TEMPERATUR, DAYA DAN WAKTU PADA PEMANAS MESIN ROASTING KOPI OTOMATIS BERKAPASITAS 5 KG: EXPERIMENTAL STUDY OF TEMPERATURE, POWER AND TIME ON THE HEATER OF AN AUTOMATIC COFFEE ROASTING MACHINE WITH CAPACITY 5 KG - Maulana Junianto; Rahmad, Hadi; Khalida, Zulfa (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2022)
A coffee roasting machine is a machine that is used to roast coffee beans to ripen. The working principle of this machine is that the coffee beans are heated in a rotating roaster with a predetermined temperaturee, so that the heating can be evenly distributed. The process of roasting coffee beans can be adjusted to temperaturee, in which the heating element of the tool uses a Band Heater component. Band Heater is shaped like a tube with a function as a heater to heat a cylinder of a certain size which has advantages such as high operating temperature, fast heating, high heat efficiency, environmentally friendly, even and accurate heating, can adjust the automatic control system. The purpose of this study was to design a controlled coffee roasting machine using an electric heating system of the band Heater type with a capacity of 5 kg and to know the PID Rex-C100 temperaturee control on a coffee roasting machine with a capacity of 5 kg. This study show temperature rise every 10 minutes during the roasting process, a graph of the difference in temperaturee every 10 minutes during the roasting process, data on the measurement of the heating system temperaturee, a graph of the relationship between the heater band temperaturee and heat flow, the comparison of the temperaturee bands. heater with roasting chamber, and graph of the required power band heater.